Legal recognition of rainwater harvesting rights: A comparative study between the United States and the European Union - Zohra, Herhira Fatima (The International tax journal, 2025)
Global interest in rainwater harvesting is steadily increasing as a sustainable approach to enhancing water security and mitigating the impacts of floods and droughts. This article seeks to analyze the legal status of the right to harvest rainwater within two distinct legal systems: the United States (a federal system based on state laws) and the European Union (a European regulatory framework with national applications). The descriptive-analytical and comparative methodologies were employed, relying on legislative texts (laws, decrees), executive regulations, judicial decisions, and academic studies issued between 2015–2025. The findings indicate that the United States suffers from significant legislative fragmentation among states and the absence of a federal framework expressly recognizing rainwater rights, whereas the European Union has taken regulatory steps in the field of treated water reuse but recognition of rainwater harvesting as an independent right remains a variable national matter. The study concludes that a tangible legal gap exists in both systems: the absence of a unified legal framework balancing the protection of traditional water rights with the promotion of sustainable harvesting mechanisms. The paper proposes legal frameworks for incorporating the “right to harvest rainwater” into water rights systems along with mechanisms for environmental protection and distributive justice.